2022
DOI: 10.1186/s12877-022-03412-w
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of self-care disability among older adults in China

Abstract: Background Self-care disability among older adults is a global public health issue. However, it lacks the up-to-date information based on nationally representative, more comprehesive data in China. Methods Using China’s 2020 population census data, this paper provides a macro-analysis of the prevalence and socio-demographic characteristics of self-care disability among older adults. Results 25.5 millio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…The second hypothesis believes that individuals with sensory dysfunction may have reduced auditory and spatial awareness of their immediate surroundings, rendering them more vulnerable to accidents and accidental injuries, in an already cognitively compromised population (Jiam et al 2016;Lubetzky 2020). The third theory is based on the effect of multisensory integration, proposing that individuals with hearing loss develop substitution strategies that make them more dependent on visual, vestibular, or somatosensory information to maintain balance (Lubetzky 2020;Zhang et al 2020;Wang et al 2022). HI, in the presence of cognitive impairment, may serve as an indicator for frailty (e.g., sensory, cognitive, and physical frailty) (Yamada et al 2016;Wang et al 2020), which is a powerful predictor of falling.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The second hypothesis believes that individuals with sensory dysfunction may have reduced auditory and spatial awareness of their immediate surroundings, rendering them more vulnerable to accidents and accidental injuries, in an already cognitively compromised population (Jiam et al 2016;Lubetzky 2020). The third theory is based on the effect of multisensory integration, proposing that individuals with hearing loss develop substitution strategies that make them more dependent on visual, vestibular, or somatosensory information to maintain balance (Lubetzky 2020;Zhang et al 2020;Wang et al 2022). HI, in the presence of cognitive impairment, may serve as an indicator for frailty (e.g., sensory, cognitive, and physical frailty) (Yamada et al 2016;Wang et al 2020), which is a powerful predictor of falling.…”
Section: Discussionmentioning
confidence: 99%
“…China’s 2020 population census revealed that the prevalence of self-care disability increases with age. The prevalence of self-care disability was 2.34% in adults aged 60 years and above, was higher than 5% in those aged 80 and above, and higher than 15% in those over 90 years (Guo et al 2022).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One potential explanation is that some Chinese older adults still hold the social norm that children should take care of them when they are sick and old. However, given the decades‐long decline in fertility rates, family sizes in China have become smaller, and family functions have weakened (Guo et al., 2022). Chinese older adults tend to recognise that totally relying on their children is not realistic because of the mobility of their children, the decrease of family sizes and the responsibilities younger generations have in modern society.…”
Section: Discussionmentioning
confidence: 99%
“…With Chinese life expectancy at 78.2 years in 2022, and the prevalence of disabilities among the elderly at 26.2% (95% CI: 23.7-28.6%) [ 1 ], Chinese parents have long life expectancies but require assistance. While 2.34% of Chinese aged over 60 years require assistance from a caregiver for daily behaviors [ 2 ], elderly depend heavily on their children for care due to a lack of care infrastructure such as nursing homes and geriatric services. Finally, the rapidity of the growth and sheer size of China’s graying population creates unique challenges.…”
mentioning
confidence: 99%